Exploring Lecturer Commitment in the Digital Era: Value, Affective, Continuance, and Normative Dimensions - Putu Gede Subhaktiyasa (Jurnal Ilmiah Profesi Pendidikan, 2025)
Digital transformation has increased the complexity of higher education dynamics, affecting various aspects, including lecturers' commitment to the institution. This study aims to analyze lecturers' commitment, including value, affective, continuance, and normative commitments, in the face of changes triggered by digitalization. This study used a descriptive quantitative approach, with data collected through a standardized questionnaire from 336 lecturers selected using a proportional random sampling technique. Descriptive statistical analysis was conducted with SPSS. The results showed that value and affective commitment had the highest levels, reflecting the alignment of lecturers' values with the institution's vision and their emotional attachment to higher education. However, continuance commitment showed variation, with some lecturers considering external factors such as other job opportunities and financial benefits in their decision to stay. Meanwhile, normative commitment tends to be low, indicating that not all lecturers feel morally obligated to their higher education institution. The findings emphasize the importance of institutional strategies in improving lecturers' welfare, continuous professional development, and incentive policies to strengthen their long-term commitment.